EGUP corrected thermodynamics of RN-AdS black hole with quintessence matter - Baoyu Tan (Physics Letters B)
Reissner-Nordström anti de Sitter (RN-AdS) black hole, characterized by electric charge and negative cosmological constant, exhibits a rich thermodynamics structure. In this paper, we consider the influence of quintessence, a hypothetical dark energy component with negative pressure. We have computed the extended generalized uncertainty principle (EGUP) corrections to the thermodynamics of RN-AdS black hole, including Hawking temperature, heat capacity, entropy function and pressure. Furthermore, as a special case of EGUP, we have computed and compared the result obtained from the generalized uncertainty principle (GUP) with those from the extended uncertainty principle (EUP). This work contributes to the understanding of the interplay between fundamental physics and the macroscopic properties of black holes, offering a novel perspective on the thermodynamics of RN-AdS black holes in the context of quintessence and quantum gravity corrections. More importantly, we found that, unlike in the case of the Reissner-Nordström (RN) black hole, the qualitative behavior for the RN-AdS black hole with quintessence remain largely unchanged, except for minor differences, at the equation of state parameters ωq=−1/3 and ωq=−2/3. In addition, unlike RN black holes, the phase transition point of RN-AdS black holes shift to almost zero.